PROSES PENEGAKAN HUKUM DAN UPAYA PENGENDALIAN MASALAH LINGKUNGAN HIDUP - H.M Erman Amin (Jurnal Cakrawala Hukum, 2017)
In environmental aspect, one of the main element is the existence of interaction and this element is called themechanic element. It is called by then, because by those element composing interaction between environmentalelements. Interaction process between human and their environment is called ecosystem. This ecosystem is notonly occurred between human and their environment, but also with other creatures. On technical pahse there aresynthesis. In this process, it is can be ignored the effect between one factor to another factor because of it will causedchain reaction to the environmental law enforcement. Beside of those factors, there are problem which occurrednaturally such as a great number of Indonesia population and separated in some lands so potentially they havedifferent law perspective, the lack of law awareness, the law enforcer itself still learn the whole part of environmentallaw, and there is problem of funding. All those problem will be tackled if there is teamwork between government,society and businessman in order to resepect the rights and do their obligation as stated in Management andProtectionof Environment Act. Naturally, human have to have high awaraness in run environmental law, aboutthemanagement and conservation. Because human has sociological and biological relation with environmentwherethey live. Even the environmental law is good, if there is no awareness it will be useless.